Tracking Control for Mobile Robots Considering the Dynamics of All Their Subsystems: Experimental Implementation - José Rafael García-Sánchez; Ramón Silva-Ortigoza; Salvador Tavera-Mosqueda; Celso Márquez-Sánchez; Victor Manuel Hernández-Guzmán; Mayra Antonio-Cruz; Gilberto Silva-Ortigoza; Hind Taud (Complexity)
The trajectory tracking task in a wheeled mobile robot (WMR) is solved by proposing a three-level hierarchical controller that considers the mathematical model of the mechanical structure (differential drive WMR), actuators (DC motors), and power stage (DC/DC Buck power converters). The highest hierarchical level is a kinematic control for the mechanical structure; the medium level includes two controllers based on differential flatness for the actuators; and the lowest hierarchical level consists of two average controllers also based on differential flatness for the power stage. In order to experimentally validate the feasibility of the proposed control scheme, the hierarchical controller is implemented via a Σ–Δ-modulator in a differential drive WMR prototype that we have built. Such an implementation is achieved by using MATLAB-Simulink and the real-time interface ControlDesk together with a DS1104 board. The experimental results show the effectiveness and robustness of the proposed control scheme.